The Effect of Local Original Revenue And Transfer Funds On Regional Expenditure In Ogan Ilir District: A Flypaper Effect Analysis (2015-2024) - Hatita Korpriana Laconi; Fauzia Afriyani; Abdul Kholik (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2026)
This study aims to analyze the influence of Local Genuine Revenue (PAD) and Transfer Funds on Regional Expenditure in Ogan Ilir Regency, as well as to identify the existence of the Flypaper Effect phenomenon during the 2015-2024 period. Using a quantitative method with a causal associative approach, this research utilizes secondary time-series data from annual Budget Realization Reports (LRA). The results of the multiple linear regression analysis show that PAD has a positive and significant effect on Regional Expenditure, with a regression coefficient of 5.766 and a significance value of 0.047. On the other hand, Transfer Funds partially do not have a significant effect on Regional Expenditure, with a significance value of 0.191. The primary finding of this study indicates that the Flypaper Effect phenomenon does not occur in Ogan Ilir Regency, as the PAD coefficient (5.766) is substantially larger than the Transfer Funds coefficient (0.836). This suggests that the local government is more responsive to increases in internal revenue than to central transfers when determining expenditure policies, reflecting efforts toward fiscal independence and rational financial management without falling into fiscal illusion.